Results of two years of water training on jump height in postmenopausal women with moderate hip risk fracture - María Carrasco Poyatos; Manuel Vaquero Abellán (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2010)
The aim of the present study was to investigate the effect of a water-based calisthenics and resistance program on jump height in postmenopausal women with moderate hip risk fracture. 39 women were divided into three groups: swimming group (GN; n = 17), calisthenics and resistance group (GIR; n = 14), and control group (GC; n = 8). Body composition test included body mass index (IMC) and waist to hip ratio (ICC). Jump height was assessed by a countermovement jump (CMJ). GN showed a significant (p<0.05) decrease in ICC (5.81%). GIR showed a significant decrease in IMC (3.65%) and a significant increase in CMJ (15.5%). Two years of water-based calisthenics and resistance training can offer significant benefits in jump height in postmenopausal women with moderate hip risk fracture. Both exercise programs can also improve body composition.